A Survey on Novel Sequestration Adroitness to Secure Susceptible Micro Data - Koujalagi, Ashok (International Journal of Computer Sciences and Engineering, 2019)
The sharing data issues with the high-quality airline props on various media outlets. The new supplier can try to collect information about the information provided by various suppliers. Revised dates are constantly increasing for conflict resolution data that keeps data specific. The plan provided community information based on the issue of unpublished collections of high-quality data from different data providers. Therefore, security, which ensures that non-media outlets are carrying out the security measures given to gather new producers. There will be customers M per customer to avoid purchasing an anonymous definition for each customer. To overcome this, there is a new system called coverage that offers better information on the use of all kinds of foods needed for high-level information.